2023
DOI: 10.3390/pr11102985
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Braking of Electric Vehicles Based on Fuzzy Control Strategy

Zongjun Yin,
Xuegang Ma,
Rong Su
et al.

Abstract: Regenerative braking technology is a viable solution for mitigating the energy consumption of electric vehicles. Constructing a distribution strategy for regenerative braking force will directly affect the energy saving efficiency of electric vehicles, which is a technical bottleneck of battery-powered electric vehicles. The distribution strategy of the front- and rear-axle braking forces of electric vehicles that possess integrated front-wheel-drive arrangements is established based on the Economic Commission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Jiang et al [71] reported that their energy recovery efficiency reached 55%. In the NEDC, Jiang et al [71] achieved an energy recovery efficiency of 55.3%, followed by Salari et al [80], Wager et al [81], Xiao et al [86], Mondal et al [84], Yin et al [70], and Xu et al [92]. Although our energy recovery efficiency is not as high as that of Jiang et al [71], it is better than others.…”
Section: Comparison Of Energy Recovery Performancementioning
confidence: 49%
“…Jiang et al [71] reported that their energy recovery efficiency reached 55%. In the NEDC, Jiang et al [71] achieved an energy recovery efficiency of 55.3%, followed by Salari et al [80], Wager et al [81], Xiao et al [86], Mondal et al [84], Yin et al [70], and Xu et al [92]. Although our energy recovery efficiency is not as high as that of Jiang et al [71], it is better than others.…”
Section: Comparison Of Energy Recovery Performancementioning
confidence: 49%
“…The output of the controller is commonly the ratio coefficient between regenerative braking torque and total braking torque. 4 , 10 13 He et al 14 introduced a neural network (NN) controller for composite braking systems aiming to enhance energy efficiency and braking stability concurrently. Simulation results revealed a 3.04% enhancement in the final SOC with the NN controller compared to the parallel braking approach, indicating superior energy efficiency.…”
Section: Introductionmentioning
confidence: 99%